Ear Acupuncture for Immediate Pain Relief—A Systematic Review and Meta-Analysis of Randomized Controlled Trials. Issue 3 (17th October 2016) - Murakami, M.; Fox, L.; Dijkers, Marcel P.
Abstract: Objective. To systematically review the literature on the effectiveness of ear acupuncture (EA) for immediate pain relief. Data sources. AMED, CINAHL, Cochrane Reviews, Embase, PsycINFO, PubMed, Scopus Web of Science, from inception through March 2015. Study selection. English publications, randomized controlled trials on human subjects involving EA as a treatment for pain, with outcomes recorded within 48 hours. Data extraction and design. Two authors independently assessed trial eligibility, quality, results, and side effects, and extracted data; a third author checked final data. Effect size (d), mean difference (MD), and 95% confidence interval (CI) were calculated. The Physiotherapy Evidence Database (PEDro) scoring system was used to assess study quality. Meta-analysis was performed for two primary outcomes measures—pain intensity score and analgesic requirements. Results. Ten studies met inclusion criteria. Quality per PEDro scores: four excellent, four good, two fair. Based on their primary outcome measures, six studies showed EA being superior to its comparator, three showed no difference to comparators (which in all cases were analgesics), and one study showed significant pain decrease at the first time point and no significant decrease at the second. Meta-analysis was completed for the three studies that evaluated pain intensity as a primary outcome measure, and EA was superior to comparator (MD = -0.96, 95% CI = -1.82– -0.11), but the MD was small. Meta-analysis was completed for the six studies that evaluated analgesic requirements, and EA was superior (MD = -1.08, 95% CI = -1.78– -0.38]), again with a small MD. Six studies reported side effects; all were minor and transient. Conclusions. Ear acupuncture may be a promising modality to be used for pain reduction within 48 hours, with a low side effect profile. Rigorous research is needed to establish definitive evidence of a clinically significant difference from controls or from other pain treatments.